Analisis Pengaruh Faktor Individu dan Faktor Komunitas Terhadap Pemberian ASI Eksklusif oleh Ibu Bayi di Wilayah Kerja Puskesmas X Tuban - Nola Agatha Tri Anggraeni Febrianti; Dewi Irma Susanti; Nyoman Anita Damayanti (Universitas Airlangga, 2024)
Background: Decreasing Infant Mortality Rate (AKB) and improving nutritional status are indicators of health development in Indonesia. This is closely related to exclusive breastfeeding of infants. In Tuban Regency, the achievement of exclusive breastfeeding decreased from 2019 to 2020, with an achievement of 79.5% to 76.7%. Success in increasing the achievement of exclusive breastfeeding involves several factors, namely individual factors and community factors in the mother's neighborhood. Objectives: Analyzed the influence of variables of maternal characteristics, attitudes, beliefs, social norms, stigma, and culture in the mother's living environment with variables of exclusive breastfeeding actions on infants in the Working Area of Puskesmas X Tuban. Methods: Conducted a cross-sectional design observational study. The sample for this study consisted of 110 mothers with babies aged 7-12 months. Individual factors and community factors served as independent variables, while the act of exclusive breastfeeding in infants was the dependent variable. The test utilized was a binary logistic regression test. Results: The result revealed several factors that were pertinent to the provision of exclusive breastfeeding. In individual factors, there was a significant association with age subvariable (0,005); expenses (0,038); and knowledge (0,006). Meanwhile, community factors showed a significant association with cultural subvariables (0,006). Exclusice breastfeeding by the baby was found to be correlated with the mother’s condition and the environment around the mother. Inadequate conditions, such as iuffcient family knowledge and income, had an impact on exclusive breastfeeding. Additionally, the culture in the surrounding environment posed as an obstacle for mothers in providing excluuve breastfeeding to ther babies. Conclusions: The practice of exclusive breasfeeding by mothers to babies is closely associated with various factor, including individual factors and community factors.